Morphology and taxonomic assessment of eight genetic clades of Mercuria Boeters, 1971 (Caenogastropoda, Hydrobiidae), with the description of five new species - Miller, Jonathan P.; Delicado, Diana; García-Guerrero, Fernando; Khalloufi, Noureddine; Ramos, Marian A. (European Journal of Taxonomy, 2023)
The freshwater snail genus Mercuria is widely distributed in lowland waters across Western Europe, Northern Africa and the Mediterranean islands. Approximately two-thirds of the currently recognised species are described based on their shell morphology, which may vary within species due to biotic and abiotic factors. Recent molecular phylogenies that included numerous previously documented populations recovered 14 species clades, nine of which correspond to nominal species and five, to undescribed taxa. Here, we formally describe the five undescribed taxa as new species and provide morphological descriptions of the shell and other anatomical structures for three of the other inferred clades and for the species M. maceana to elucidate their taxonomic status and assess the utility of morphological characters for species delimitation in Mercuria. Taken together, the morphological and molecular evidence suggest new identifications and synonymies, having implications on the known geographic range of the studied species, including the type species M. similis. Anatomical measurements and geometric morphometric analysis of shell shape revealed no clear differentiation among the species analysed, predicting the importance of molecular data in elucidating the species diversity of the genus.